2008
DOI: 10.1185/03007990802081675
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical and economic outcomes of admission hyponatremia among hospitalized patients

Abstract: Hyponatremia is common at admission among hospitalized patients and is independently associated with a 55% increase in the risk of death, substantial hospital resource utilization and costs. Potential for bias inherent in the retrospective cohort design is the main limitation of our study. Studies are warranted to explore how prompt normalization of [Na(+)] may impact these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
128
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 19 publications
9
128
3
1
Order By: Relevance
“…As indicated by the divergent results of previous studies, the prevalence of hyponatremia is highly influenced by study population composition (4,12), criteria applied to define hyponatremia at hospital admission (3,4), and composition of the denominator (i.e. whether only patients for whom serum sodium was measured were included) (3,4,6,12). The 15% overall prevalence of hyponatremia observed in our study is comparable with that observed among 2171 internal medicine patients in a recent single-center study (5).…”
Section: European Journal Of Endocrinologysupporting
confidence: 73%
See 1 more Smart Citation
“…As indicated by the divergent results of previous studies, the prevalence of hyponatremia is highly influenced by study population composition (4,12), criteria applied to define hyponatremia at hospital admission (3,4), and composition of the denominator (i.e. whether only patients for whom serum sodium was measured were included) (3,4,6,12). The 15% overall prevalence of hyponatremia observed in our study is comparable with that observed among 2171 internal medicine patients in a recent single-center study (5).…”
Section: European Journal Of Endocrinologysupporting
confidence: 73%
“…Mortality risk was increased across virtually all major primary discharge diagnosis groups and categories of previous morbidity. As indicated by the divergent results of previous studies, the prevalence of hyponatremia is highly influenced by study population composition (4,12), criteria applied to define hyponatremia at hospital admission (3,4), and composition of the denominator (i.e. whether only patients for whom serum sodium was measured were included) (3,4,6,12).…”
Section: European Journal Of Endocrinologymentioning
confidence: 97%
“…The results of this study are consistent with others in showing that HN patients use healthcare services more extensively, and represent a patient population which is more expensive to treat in the inpatient setting. 5,22 Additionally, this study yields new findings in that patients in the real-world with hyponatremia resulting from various etiologies are more likely to be readmitted to the hospital than patients with similar demographics and characteristics who do not have hyponatremia. The results of the subgroup analysis were generally consistent with the results for the overall matched population, as the incremental burden estimates were directionally consistent.…”
Section: Discussionmentioning
confidence: 79%
“…Zilberberg et al and Callahan et al additionally reported that HN patients had a significantly greater need for ICU (4%-10%). 5,22 In the present study, LOS in the ICU and associated costs were also compared among HN and non-HN cohorts and, after adjustment for key patient characteristics, hyponatremia was associated with an incremental increase of 10.2% for ICU LOS and an 8.9% increase in ICU cost.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation